Modern forms of committing genocide as an international crime (on the example of analysis of the practice of application of the 1948 UN Convention) - Amanzholov, Zh.M.; Adibayeva, A.K.; Ryssaldiyeva, A.Ye. (Bulletin of the Karaganda University “Law Series”, 2022)
The article examines the principal points of implementing the provisions of the United Nations Convention on Genocide in the Criminal Code of the Republic of Kazakhstan in designations of the initial punishable forms of participation in the commission of this international crime. In this regard, the authors analyzed the ratio of articles of both the universal international agreement and the Criminal Law of the Republic of Kazakhstan in terms of compliance with each other using the decision of international ad hoc criminal tribunals for the former Yugoslavia and Rwanda. Special attention is paid to the fact that the current Criminal Code of the Republic of Kazakhstan, contempting the integration of general provisions on criminal responsibility for their commission, does not accommodate formal adaptation of the norms of the Convention on conspiracy to commit genocide, public and direct incitement to commit genocide, attempted genocide and complicity in genocide. It is emphasized that given the sufficient availability of international case law on these truncated compositions, the Republic of Kazakhstan, as a state party to the Convention, has a need and opportunity to provide them in a special part of the Criminal Code as independent signs of the objective side of the crime of genocide.